Paleomagnetic evidence for vertical‐axis rotations of crustal blocks in the Woodlark Rift, SE Papua New Guinea: Miocene to present‐day kinematics in one of the world's most rapidly extending plate boundary zones. (3rd July 2015) - Cairns, Elizabeth A.; Little, Timothy A.; Turner, Gillian M.; Wallace, Laura M.; Ellis, Susan
Abstract The continental Woodlark Rift, in SE Papua New Guinea lies west of a propagating oceanic spreading center in the Woodlark Basin and is currently one of few places on Earth where active continental breakup is thought to be occurring. Here north‐south extension is localized on a few major normal faults. We determined characteristic remanent magnetization (ChRM) components from demagnetization profiles of >300 individual specimens. From these, 157 components contribute to paleomagnetic directions for six formations. We compare Early Miocene (∼20 Ma) to Late Pliocene (3.0 ± 0.5) ChRM mean directions, at four localities, with contemporaneous expected field directions corresponding to the Australian Plate. Time‐varying finite rotations from Cape Vogel Peninsula (28–12°) suggest anticlockwise rotation had begun by ∼15 Ma. This rotation may have been accompanied by rifting, ∼7 Ma earlier than previously inferred. Furthermore, that early extension may have occurred south of the present rift, and that deformation later migrated north of the Peninsula. Pliocene vertical‐axis rotations are consistent with GPS‐determined plate motions, suggesting that contemporary rift kinematics were established by ∼3 Ma. Finite anticlockwise rotation (10.1 ± 7.6°) in the Amphlett Islands is accordant with seafloor spreading in the Woodlark Basin, suggesting this locality has seen the full Woodlark plate motion since 3 Ma. Clockwise rotation of the Goodenough Bay Block (−6.5 ± 11.2°) since the Late Miocene has accomplished transfer of deformation between major extensional corridors, and an especially rapid local rotation (−16.3 ± 9.5°) in NW Normanby Island may suggest an incipient dextral transfer fault.